1983
DOI: 10.1093/jac/12.suppl_a.101
|View full text |Cite
|
Sign up to set email alerts
|

A randomized study of ceftazidime compared to ceftazidime and tobramycin for the treatment of infections in cancer patients

Abstract: Three hundred and twenty-one febrile episodes in cancer patients were treated with ceftazidime alone or in combination with tobramycin. Patients were grouped according to their neutrophil count into neutropenic and non-neutropenic (less than 1000 and greater than 1000/mm3) respectively. Two hundred and seventy-five episodes were evaluated. The overall response rate in 83 episodes of infection treated with ceftazidime alone was 60 and 73% in those who received the combination. In those bacteriologically proven … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
28
0

Year Published

1985
1985
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(32 citation statements)
references
References 0 publications
4
28
0
Order By: Relevance
“…The ability of this organism to simultaneously express multiple mechanisms of resistance adds to the challenge of effectively treating it (104,157). Several studies evaluating morbidity and mortality with dual and single antipseudomonal agents for the treatment of P. aeruginosa infections have been conducted, as outlined below (7,15,44,70,112,152,180,211,224,227,228,246).…”
Section: Pseudomonas Aeruginosa Infectionsmentioning
confidence: 99%
“…The ability of this organism to simultaneously express multiple mechanisms of resistance adds to the challenge of effectively treating it (104,157). Several studies evaluating morbidity and mortality with dual and single antipseudomonal agents for the treatment of P. aeruginosa infections have been conducted, as outlined below (7,15,44,70,112,152,180,211,224,227,228,246).…”
Section: Pseudomonas Aeruginosa Infectionsmentioning
confidence: 99%
“…These included early studies with moxalactam, cefotaxime, and ceftozixime. Even studies using more suitable broad-spectrum cephalosporins (e.g., ceftazidime and cefoperozone) have been somewhat limited by small numbers of entries or by comparison with suboptimal drug regimens, although a collective data base is emerging (8,11,12,14,19,28,36,39,43,44).…”
Section: Monotherapeutic Options For Empiricalmentioning
confidence: 99%
“…However, some newer cephalosporins, including ceftazidime, with very good antipseudomonal activity have been suggested as monotherapy for the treatment of severe pseudomonas infections (5,(11)(12)(13). Recent clinical trials have shown ceftazidime monotherapy to be as successful as standard combination therapy in the treatment of infections with gram-negative rods (5,13).…”
mentioning
confidence: 99%